Evaluation of trained small-scale commercial pig feed producers in Uganda - Lukuyu, Ben A.; Businge, Martha; Ahumuza, Ronnie; Ouma, Emily A. (International Livestock Research Institute, 2024)
The livestock subsector is significant in Uganda’s agriculture industry and contributes substantially to the livelihoods of the country’s population. Despite the rising demand for livestock-related products such as milk, meat, and eggs, livestock production in Uganda nevertheless remains low. Several factors have been identified as restricting livestock output, including poor nutrition, which is frequently associated with inadequate feed quality and quantity (MAAIF 2005). In order to increase production, farmers have frequently been compelled to feed livestock with commercial animal feeds (Kabi et al. unpublished). As a result, the production of commercial animal feed and concentrates by small-scale feed producers has been on the rise for the last decade. Small-scale feed producers have flourished as a result of their proximity to farmers and the feed producers’ ability to provide tailor-made concentrate feeds that are affordable to farmers. While small-scale feed producers have benefited from changes brought about by the emergence and expansion of the commercial animal feed industry, new challenges, such as a lack of technical expertise in feed formulation and mixing, and unregulated concentrate feed production and supply have emerged. Lack of technical expertise and feed quality regulation policies have often resulted in supply of poor-quality feeds to livestock farmers, hence persistent low productivity of livestock farms that depend on commercial feeds has been observed.